The Relationship Between Emotional Intelligence, Social Intelligence And Self-Efficacy Among Preservice English Teachers - Özel, Kübra (Eğitim Bilimleri Enstitüsü, 2019)
Due to the awareness of the significance of emotional intelligence and social intelligence in educational context, several studies have been conducted on these two constructs. Research findings have revealed that they greatly contribute to teaching and learning processes in many aspects. The aim of to current study is to investigate the relationship between social intelligence, emotional intelligence, and self-efficacy beliefs among Turkish EFL preservice teachers. The present study was carried on 200 preservice teachers majoring in ELT department at Hacettepe University. To determine the emotional intelligence of preservice teachers, Turkish version of The Schutte Self-Report Emotional Intelligence Test which is a scale created by Schutte, Malouff, Hall, Haggerty, Cooper, Golden and Dornheim (1998) was employed. Simultaneously, a questionnaire entitled Teachers’ Sense of Efficacy Scale which is created by Tschannen-Moran and Woolfolk-Hoy (2001) was used with the aim of evaluating self-efficacy beliefs of preservice teachers. Finally, to determine their social intelligence, Tromso Social Intelligence Scale created by Silvera, Martinussen, & Dahl (2001) was used. All the scales were translated into Turkish. For data analysis process, statistical techniques such as mean, standard deviation, percentage, and frequency were employed in the study. Findings revealed that there is a strong positive relationship between their EQ and SQ levels (R=,624, p<,05), a moderate level positive correlation between the total level of teacher efficacy and SQ ( R=,413, P<,005), and a moderate level positive relationship between their EQ and teacher efficacy of preservice English teachers (R=,624, p<,05). Table of Contents Abstract ii Öz iii Acknowledgements iv Table of Contents v List of Tables viii Symbols and Abbreviations x Chapter 1 Introduction 1 Statement of the Problem 3 Aim and Significance of the Study 4 Research Questions 4 Sub-Research Questions 5 Assumptions 5 Delimitations 5 Limitations 6 Definitions 6 Chapter 2 Literature Review 8 Emotional and Social Intelligence 8 Emotional Intelligence 8 History of emotional intelligence 8 Models of emotional intelligence 11 Salovey and Mayer model 11 Goleman's Mixed modelof emotional intelligence 14 The Bar-On model of emotional intelligence. 16 Criticisms of emotional intelligence. 18 Social Intelligence 19 History of social intelligence 19 Delimitations of social intelligence. 23 The Relationship between Emotional Intelligence and Social Intelligence .24 Significance of emotional and social intelligence in general education .26 Self-Efficacy 40 History of self-efficacy. 40 Teacher efficacy and its significance. 41 Building self-efficacy through training. 46 The relationship between teacher self-efficacy and effective teaching. 49 Efficacy beliefs of preservice teachers. 52 Related Studies. 53 The relationship between emotional intelligence, social intelligence and teacher efficacy. 53 Chapter 3 Methodology 56 Introduction. 56 Setting and Participants 56 Data Collection 57 Instruments 58 Intrument 1 the Schutte Emotional Intelligence Scale. 58 Instrument 2 the Teacher'S Sence of Efficacy ScaleData 58 Instrument 3 the Tromso Social Intelligence Scale. 59 Data Analysis. 59 Chapter 4 Findings 61 Introduction. 61 Reliability of Research Instruments 61 Factor Analysis of Scales 62 Factor analysis of the Schutte Emotional Intelligence Scale 62 Factor analysis of the Teachers' Sense of Efficacy Scale 64 Factor analysis of The Tromso Social Intelligence Scale 66 Findings Related to Research Questions 68 Findings related to sub-research questions 68 Chapter 5 Conclusion, Discussion and Suggestions 77 Conclusions and Discussion. 77 Suggestions 80 References 83 APPENDIX-A: Ethics Committee Approval 98 APPENDIX B: Declaration of Ethical Conduct 99 APPENDIX-C: Thesis Originality Report 100 APPENDIX-D: Yayımlama ve Fikrî Mülkiyet Hakları Beyanı 101 Duygusal ve zekânın eğitim alanındaki rolü üzerine ilginin gün geçtikçe artmasıyla birlikte, bu iki olgu üzerine pek çok çalışma yürütülmüştür. Elde edilen sonuçlar bu iki olgunun öğretme ve öğrenme süreçlerine birçok açıdan büyük oranda katkı sağladığını ortaya koymuştur. Mevcut çalışma ise duygusal zekâ, sosyal zeka ve İngilizce öğretmenlerinin öz yeterlik inançları arasındaki ilişkiyi incelemeyi hedeflemektedir. Bu çalıma Hacettepe Üniversitesi’nde İngilizce öğretmenliği bölümünde eğitim almakta olan 200 öğretmen adayı üzerinde uygulanmıştır. Öğretmen adaylarının duygusal zeka değerlerini belirlemek için Schutte, Malouff,Hall, Haggerty, Cooper, Golden ve Dornheim (1998) tarafından geliştirilen Schutte Duygusal Zekâ Ölçeği kullanılmıştır. Aynı zamanda Öğretmenler Öz-yeterlik Ölçeği adında Tschannen-Moran and Woolfolk-Hoy (2001) tarafından geliştirilen ölçek Öğretmen adaylarının özyeterlilik inançlarını değerlendirmek için kullanılmıştır. Ve son olarak öğretmen adaylarının sosyal zekâlarını belirlemek için Silvera, Martinussen, & Dahl (2001)’ nın geliştirdiği Tromso Sosyal Zeka Ölçeği kullanılmıştır. Tüm ölçekler Türkçe’ye çevirilmiştir. Verileri analiz etmek için, standart sapma, ortalama, yüzdelik ve sıklık gibi istatistiksel teknikler kullanılmıştır. Bulgular duygusal ve sosyal zeka arasında güçlü bir pozitif ilişki (R=,624, p<,05), öğretmen özyeterliliği ve sosyal zeka arasında orta derecede bir pozitif ilişki (R=,413, p<,005) ve İngilizce öğretmen adaylarının duygusal zeka ve öğretmen özyeterlilikleri arasında orta derecede bir pozitif ilişki olduğunu ortaya koymuştur.